1986
DOI: 10.1121/1.393683
|View full text |Cite
|
Sign up to set email alerts
|

Lateralization of low-frequency tones and narrow bands of noise

Abstract: It is well known and universally accepted that people's ability to use ongoing interaural temporal disparities conveyed via pure tones is limited to frequencies below 1600 Hz. We wish to determine if this limitation is the result of the constant amplitude and periodic axis-crossings which characterize pure tones. To this end, an acoustic pointing task was employed in which listeners varied the interaural intensitive difference of a 500-Hz narrow-band noise (the pointer) so that the position of its intracranial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
10
0

Year Published

2001
2001
2021
2021

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 35 publications
(13 citation statements)
references
References 16 publications
3
10
0
Order By: Relevance
“…Several psychophysical studies have addressed ITD-induced lateralization of bands of noise of varying center frequency and bandwidth. To the extent that ITD-induced lateralization reflects sensitivity to ITDs, these psychophysical data show exactly the same bandwidth effects as our neural thresholds: at low frequencies (<1,600 Hz), the effect of bandwidth on lateralization is marginal (Schiano et al 1986); at high frequencies (4 and 8 kHz), the amount of lateralization increases markedly with bandwidth (Bernstein and Trahiotis 2003). …”
Section: Discussionsupporting
confidence: 74%
“…Several psychophysical studies have addressed ITD-induced lateralization of bands of noise of varying center frequency and bandwidth. To the extent that ITD-induced lateralization reflects sensitivity to ITDs, these psychophysical data show exactly the same bandwidth effects as our neural thresholds: at low frequencies (<1,600 Hz), the effect of bandwidth on lateralization is marginal (Schiano et al 1986); at high frequencies (4 and 8 kHz), the amount of lateralization increases markedly with bandwidth (Bernstein and Trahiotis 2003). …”
Section: Discussionsupporting
confidence: 74%
“…A 1300 Hz limit for following temporal signals is also found in studies of sound localization wherein the timing of signals is compared between the ears (Zwislocki and Feldman, 1956). Interestingly, such localization is dependent on the carrier timing and independent of envelope timing (Schiano et al, 1986).…”
Section: Envelope Ffr and Spectral Ffrmentioning
confidence: 92%
“…They were merely to report the apparent intracranial azimuth of each tone. This task does not have the history of use as pointing tasks used by other authors (e.g., Yost, 1981;Schiano et al, 1986), and it is an empirical question as to whether the present task provides measures of perceived intracranial location with the reliability of the earlier methods. The data obtained in present study were, however, quite orderly and systematic, and showed no obvious biases in control (pre-adaptation) conditions.…”
Section: Design and Procedure: Experimentsmentioning
confidence: 94%